LA TRANSMISIÓN TEXTUAL DE LAS COPLAS A LA MUERTE DE CARTAGENA DE FERNÁN PÉREZ DE GUZMÁN (ID 1937): VARIACIONES Y CONTEXTOS. - López Casas, Maria Mercè (Estudios Románicos, 2024)
Study of the textual transmission of the poem written by Fernán Pérez de Guzmán on the death of his master and friend Alfonso de Cartagena. The manuscripts and printed testimonies that include the poem are presented, also studying what other texts by the author are in them. The variants and variations of the poem's text are analyzed in their context.